2019
DOI: 10.18321/ectj820
|View full text |Cite
|
Sign up to set email alerts
|

Methodology of the Experiments to Study Lithium CPS Interaction with Deuterium Under Conditions of Reactor Irradiation

Abstract: Problems of plasma-facing materials degradation and in-vessel element destructions, tritium accumulation and plasma pollution can be overcome by the use of liquid metals with low atomic number. The best candidate as a material for divertor receiving plates and other in-vessel devices is lithium. One of the problems associated with the use of such lithium systems in the fusion reactors is to determine the parameters of the working gases interaction with plasma facing surfaces under conditions simulating real op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Materials science studies conducted as part of the implementation of international programs for the creation of fusion reactors ITER and DEMO have shown that one of the best materials for use as an PFM (plasma-facing material) [1] in controlled fusion plants is liquid lithium and materials based on it [2,3,4]. The use of liquid lithium as a plasma-facing material is especially promising if lithium is enclosed in a so-called capillary-porous system (CPS) [5,6].Currently, there are many studies in the world conducted with lithium CPS, which once again confirms the interest in this material [7,8,9,10,11,12,13].Work on this topic is also being carried out at the Kazakhstan Materials Science Tokamak KTM [14,15,16,17,18,19,20]. The installation is currently the only tokamak in the world designed to solve problems in the field of thermonuclear materials science.…”
Section: Introductionmentioning
confidence: 95%
“…Materials science studies conducted as part of the implementation of international programs for the creation of fusion reactors ITER and DEMO have shown that one of the best materials for use as an PFM (plasma-facing material) [1] in controlled fusion plants is liquid lithium and materials based on it [2,3,4]. The use of liquid lithium as a plasma-facing material is especially promising if lithium is enclosed in a so-called capillary-porous system (CPS) [5,6].Currently, there are many studies in the world conducted with lithium CPS, which once again confirms the interest in this material [7,8,9,10,11,12,13].Work on this topic is also being carried out at the Kazakhstan Materials Science Tokamak KTM [14,15,16,17,18,19,20]. The installation is currently the only tokamak in the world designed to solve problems in the field of thermonuclear materials science.…”
Section: Introductionmentioning
confidence: 95%